2021
DOI: 10.1093/burnst/tkab004
|View full text |Cite
|
Sign up to set email alerts
|

Obstruction of the formation of granulation tissue leads to delayed wound healing after scald burn injury in mice

Abstract: Background Delayed wound healing remains a common but challenging problem in patients with acute or chronic wound following accidental scald burn injury. However, the systematic and detailed evaluation of the scald burn injury, including second-degree deep scald (SDDS) and third-degree scald (TDS), is still unclear. The present study aims to analyze the wound-healing speed, the formation of granulation tissue, and the healing quality after cutaneous damage. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…[ 31 ] Previous studies proved that the complete healing in deep second‐degree burn wounds model needs to take more than 25 days. [ 32 ] Therefore, H&E staining results demonstrated that PCL+5ZS nanofibrous scaffolds could effectively accelerate the wound healing process and promote re‐epithelialization, exhibiting great potential for promoting burns wound healing.…”
Section: Resultsmentioning
confidence: 99%
“…[ 31 ] Previous studies proved that the complete healing in deep second‐degree burn wounds model needs to take more than 25 days. [ 32 ] Therefore, H&E staining results demonstrated that PCL+5ZS nanofibrous scaffolds could effectively accelerate the wound healing process and promote re‐epithelialization, exhibiting great potential for promoting burns wound healing.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the burn wounds in Blank and Gel groups were covered by scars without intact structure of dermis and epidermis. The previous studies have presented that the re-epithelialization strongly associated to the formation of granulation tissue[ 54 , 55 ]. Therefore, rapid filling of granulation tissue in the wound sites probably contributed to timely tissue regeneration in the 5DE-Gel group, while the wound-healing progress was postponed without positive intervention in the other two groups.…”
Section: Resultsmentioning
confidence: 99%
“…Burns damage the skin and internal organs caused by thermodynamic changes, chemicals, and electricity. Patients with extensive burns are prone to infection and sepsis, and the key to treatment is to accelerate wound closure to reduce exposure to the environment 164 . Since stem cells significantly promote wound healing, exosomes' role in burn wound healing has also attracted attention 165 , 166 .…”
Section: Introductionmentioning
confidence: 99%